A pragmatic assessment of livelihood status in the peri-urban interface: a case from developing India. Issue 1 (2nd January 2017) - Banu, Nasrin; Fazal, Shahab
ABSTRACT: The present study is an attempt to depict the picture of livelihoods and its sustainability in the transforming economy of peri-urban interface (PUI). The study assumes that process of peri-urbanization adds complexity to household livelihood security and the process of peri-urbanization has been considered as stress. To measure this stress, the study adopts the Sustainable Livelihood Approach targeted to understand the livelihood status of households. It also evaluates the coping strategies adopted by households for surviving in transforming economic and social PUI environment.